Izbira iztočnic v angleško-slovenskih in slovensko-angleških slovarjih za slovenske priseljence v ZDA - Vrbinc, Alenka (Slovenski jezik, 2025)
This article analyzes four English–Slovenian and Slovenian–English dictionaries compiled by Viktor/Victor Kubelka, Silvester Košutnik, and Frank (Javh-)Kern, intended for Slovenian immigrants in the USA. These dictionaries were published between 1904 and 1919, a period when Slovenian emigration to the USA was at its peak. The study examines similarities and differences between the word lists of the analyzed dictionaries and those of dictionaries already available on the market at the time. The focus is primarily on the selection of entries, which were presumably borrowed from existing dictionaries. We aim to determine whether a specific trend or pattern can be observed, whether the compilers’ decisions aligned with the needs of the target users—Slovenian immigrants in the USA, and whether the users could access information about the new sociocultural context. Through case analysis, we found that Kubelka’s 1912 dictionary and Kern’s 1919 dictionary most comprehensively include appropriate sociocultural equivalents; therefore, they most deserve to be called immigrant dictionaries.
Keywords: bilingual dictionary; borrowed lemmata; dvojezični slovar; immigrant dictionary; informacije o družbi in kulturi dežele priseljevanja; information about society and culture in the country of immigration; izbor iztočnic; izposojanje iztočnic; lemma choice; slovar za priseljence